Síndrome de Burnout e autoeficácia: um estudo com profissionais de enfermagem de hospitais privados de Natal/RN - Lima, Carla Fernanda de (2009)
This research verifies the influence of the self-efficacy level on burnout syndrome incidence in relation to nursing professionals from private hospitals located in the Municipality of Natal, State of Rio Grande do Norte. The nature of the research was descriptive, and the used data analysis method was quantitative which was developed through SPSS computational package, version 17.0. The used instrument for the investigation was Maslach-Burnout Inventory (MBI), and the General Perceived Self-efficacy Scale (GPSES) was applied to a sample formed from 230 nursing professionals. The statistic techniques to data analysis were: frequency analysis; factor analysis; Cronbach.s alpha; Kaiser-Meyer-Olkin test (KMO); Bartlett efericity test; percentual analysis; Spearman rank correlation analysis; and simple regression. The achieved factors from factor analysis of MBI were the same, taking into account the dimensions which Maslach initially suggested to the instrument (emotional exhaustion, lack of personal realization, and depersonalization). However, one highlights that the low internal consistence of the depersonalization dimension can occur from people.s difficulty (caused by cultural aspects) of assuming this attitude in their work environment. Through GSE, it was achieved a factor which confirmed the unidimensionality showed by the author of the instrument. In relation to the syndrome incidence, it was verified that about 50% of the researched sample presented burnout syndrome evidence. Referring to self-efficacy level, about 65% of the researched sample presented low level of self-efficacy, what can be explained by the work characteristics of these professionals. In relation to the self-efficacy influence on the Burnout syndrome, it was verified that self-efficacy can be one of the aspects which influences occupational stress chronification (burnout), mainly to the personal realization dimension. Therefore, the researched hospital organizations need reflect about their attitudes in respect to their professionals, since the numbers showed a dangerous tendency regarding a predisposition to burnout syndrome of their staff, what implies not only a significant amount of individuals who can present high levels of emotional exhaustion, lack of personal realization, and depersonalization, but also the fact that this group presents low level of self-efficacy